Early Treatment Protocol for Skeletal Class III Malocclusion - Oltramari-navarro, Paula Vanessa Pedron; Almeida, Renato Rodrigues De; Conti, Ana Cláudia De Castro Ferreira; Navarro, Ricardo De Lima [UNESP]; Almeida, Marcio Rodrigues De; Fernandes, Leandra Sant'anna Ferreira Parron (Fundação Odontológica de Ribeirão Preto, 2013)
Skeletal Class III malocclusion, with its unpredictable and unfavorable nature, has been characterized by a growth pattern with doubtful prognosis regarding orthodontic mechanics, even when performed early. For a long time, Class III malocclusion was regarded as a synonym of mandibular prognathism, regardless of the affected skeletal structures. Mandibular growth, essentially determined by genetic factors, could barely be controlled by early orthodontic interventions. Therefore, the treatment choice was to wait for the patient to grow, and then make an orthodontic intervention associated with an orthognathic surgery. Maxillary involvement in the etiology of Class III malocclusion was conclusive to change orthodontic therapeutics. Maxillary intramembranous growth has a better response to orthopedic treatment, based on growth control and redirection, thus contributing for early intervention success. In several cases, excellent results have been achieved with rapid maxillary expansion and protraction. The aim of this study was to describe and discuss the treatment of a patient with Class III malocclusion, whose treatment planning comprised two phases: interceptive (mechanical orthopedic appliances) and comprehensive (fixed orthodontic appliance). The results of this case showed that Class III malocclusion should be intercepted as early as possible to permit growth redirection, mainly when the maxilla is the primary etiologic factor or dental and/or functional factors are involved. Diagnosis, treatment planning and prognosis depend on patient age, growth potential and severity of malocclusion. Early intervention, adequate indication of appliances, and patient compliance are key factors for good outcomes.
Keywords: orthodontic interceptive; malocclusion; Angle Class III; palatal expansion technique